Perioperative utility of amisulpride and dopamine receptor antagonist antiemetics-a narrative review - Murad Elias; Alexa Gombert; Sulaimaan Siddiqui; Sun Yu; Zhaosheng Jin; Sergio Bergese (Frontiers Media S.A., 2023)
Despite advances in antiemetics and protocolized postoperative nausea vomiting (PONV) management, it remains one of the most common postoperative adverse events. In patients who developed PONV despite antiemetic prophylaxis, giving a rescue treatment from the same class of medication is known to be of limited efficacy. Given the widespread use of 5-HT3 antagonists as PONV prophylaxis, another class of effective intravenous rescue antiemetic is in dire need, especially when prophylaxis fails, and rescue medication is utilized. Dopamine antagonists were widely used for the treatment of PONV but have fallen out of favor due to some of their side effect profiles. Amisulpride was first designed as an antipsychotic medication but was found to have antiemetic properties. Here we will review the historical perspective on the use of dopamine receptor antagonist antiemetics, as well as the evidence on the efficacy and safety of amisulpride.